Identification and Assessment of the Effectiveness of Instruments Children with Special Needs Based Decision Support System (DSS) Disorders in Children with Physical and Motor Disabilities - Dewi Sri Rejeki (The Center for Disability Studies and Services Brawijaya University, 2019)
This article is part of a research and development aimed at develop the instrument identification and assessment of children with motor disorders based decision support system (DSS). This study aims to determine the effectiveness of the instruments of identification and assessment of children with special needs (ABK) based DSS in children with physical and motor disorders .The research was conducted in 10 districts / cities in Central Java province, which is taken by purposive sampling in 16 schools (SLB) and Inclusive Schools and the sample of 40 teachers. Collecting data using DSS application eligibility questionnaire instrument for the identification and assessment of children with physical and motor disorders. The use of questionnaires after teachers applying / using software identification and assessment instruments based DSS in children with physical and motor disorders. Feasibility DSS application instrument for identification of children with physical and motor disturbances seen from the aspect Visible, Interesting, Simple, Useful, Accurate, Legitimate, Structure. Methods of data analysis using quantitative descriptive technique.